Assessing value creation through NAfMA: selected case studies of Malaysian firms / Suzana Sulaiman, Normah Omar, Ibrahim Kamal Abdul Rahman - Sulaiman, Suzana; Omar, Normah (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
This paper describes the National Award for Management Accounting (NAfMA) in Malaysia and illustrates its principles with three case studies of award-winning firms. The purpose of NAfMA is to assess, draw attention to and promote improvements in management accounting techniques that enhance value creation in firms. The paper contains an account of some features of management accounting practices in the case studies.